الخصائص السيكومترية لمقياس تقدير النشاط الزائد ونقص الانتباه لدى الأطفال المتخلفين ذهنيا درجة خفيفة دراسة ميدانية بـ: المركز النفسي البيداغوجي للأطفال المعوقين ذهنيا –بوسعادة- - شريكي امال; بن زيان عائشة; اشراف: نش حدة (جامعة محمد بوضياف -المسيلة, 2025)
هدفت الدراسة الحالية الى التعرف على الخصائص السيكومترية لمقياس النشاط الزائد و نقص الانتباهلدى الاطفال المتخلفين ذهنيا درجة خفيفةالمعد من طرف (سمر رجب عزوز محمد، 2021) ومدى اتفاقها مع خصائص المقياس الجيد، ولتحقيق أهداف الدراسة استخدمنا المنهج الوصفي، وتم تطبيق المقياس على عينة قوامها 40 طفل من المركز النفسي البيداغوجي للأطفال المتخلفين ذهنيا بوسعادة للعام الدراسي 2023-2024تم اختيارهم بطريقة قصدية، وبعد المعالجة الإحصائية للبيانات المتحصل عليها باستخدام مجموعة من الأساليب الإحصائية منها: معامل ارتباط برسون للفقرات مع الدرجة الكلية للبعد والأبعاد مع الدرجة الكلية للمقياس، معامل ثبات المقياس (حساب التجزئة النصفية باستخدام معادلة سبيرمان براون وجيتمان ومعامل ألفا كرونباخ)، و توصلت الدراسة إلى النتائج التالية: مقياس النشاط الزائد ونقص الانتباه صادق وهذا ما دلت عليه نتائج صدق الاتساق الداخلي للعبارات والأبعاد مع الدرجة الكلية. مقياس النشاط الزائد ونقص الانتباه بدرجة عالية ثابت وهذا مادلت عليه المؤشرات المتحصل عليها من حساب الثبات كمعامل ألفا كرونباخ والتجزئة النصفية. الكلمات المفتاحية الخصائص السيكومترية – النشاط الزائد – نقص الانتباه – الأطفال المتخلفين ذهنيا Abstract The current study aimed to identify the psychometric characteristics of the scale of hyperactivity and attention deficit in Mentally Retarded Children of a mild degree prepared by (Samar Rajab Azouz Mohammed, 2021) and the extent of their agreement with the characteristics of a good scale, and to achieve the goals of the study, we used a descriptive curriculum, and the scale was applied to a sample of 40 children from the psycho-pedagogical Center for mentally retarded children happily for the academic year 2023-2024 among them: The Pearson correlation coefficient of the paragraphs with the total degree of dimension and the dimensions with the total degree of the scale, the scale stability coefficient (calculation of the half-hash using the Spearman-Brown-Getman equation and the cronbach Alpha coefficient), and the study reached the following results : The measure of hyperactivity and attention deficit is honest, and this is evidenced by the results of the truthfulness of the internal consistency of phrases and dimensions with the overall score. The measure of hyperactivity and attention deficit to a high degree is constant, and this is evidenced by the indicators obtained from the calculation of constancy as the cronbach's Alpha coefficient and the half-hash. Key words : Psychometric characteristics - hyperactivity – attention deficit-mentally retarded children